Problems of Inclusive Legal Services for Persons with Disabilities - Nur Paikah (Journal of Indonesian Scholars for Social Research, 2024)
This research aims to describe the condition of vulnerable groups of persons with disabilities who are in conflict with the law in obtaining the right of access to justice in law as an effort to fulfill equal rights to the law without discrimination. This research can contribute to stakeholders in order to formulate policies and legal service programs that are equitable for persons with disabilities who are in conflict with the law in order to increase access to justice for vulnerable groups of persons with disabilities. This research is a normative and sociological empirical legal research. This research examines primary, secondary, and tertiary legal materials. Processing of legal materials using legislation, concepts, philosophy, and comparative legal approaches. The results of the study found that the implementation of the fulfillment of the right of access to legal services for persons with disabilities has not been fully optimal, especially the right of access to legal assistance specifically for the deaf and speech impaired with several indicators, namely legal services have not been evenly accessible, assistance and interpreters are not yet available according to the needs of persons with disabilities.